5 - Media Image and Social Integration of Liberian and Togolese Refugees in Ghana - Heidi G. Frontani,; Kristine Silvestri,; Amanda Brown, (Africa Media Review, 2009)
In the 1990s, refugees throughout West Africa originated largely from Liberia and Togo. This article explores the reception of Liberian and Togolese refugees in one West African country – Ghana – from 1990-2007. It focuses attention on the role of Ghana’s print media, both state- and private-owned, in fostering or hindering the social integration of refugees. Ghanaian newspapers, radio broadcasts, United Nations reports and semi-structured interviews were used to build on studies of politics of belonging and relationship between ethnic identity and social integration among migrants to Ghana. It was found that Ghanaian media framed Liberia’s largely Krahn and Mandingo refugees as security threats, mercenaries and criminals, but not Togo’s Ewe refugees. Ghana’s ties to the Ewe people built hostility towards Togo’s anti-Ewe regimes, while Ghana supported Liberia’s anti-Krahn and Mandingo regimes. Liberians’ social integration was thwarted not only by Ghana’s good relations with the Liberian government, but also by media framing, lack of historical ties, internal dissent, cultural values opposed to Ghanaians and long term dependency on large United Nations organized settlements. Conversely, Togolese refugees self-settled with Ghanaian Ewe and quickly became self-sufficient in Ghana’s Volta region, once a part of Togo. The media can support social integration and more humane policies toward refugees by framing issues in human rights rather than security terms.